The Relationship Between Linguistic Intelligence and Creative Thinking (Case Study at Man 1 Kota Serang, Indonesia) - Jarnudi, Kholid; Amrudin, A (Titian: Jurnal Ilmu Humaniora, 2024)
This research aims to investigate the relationship between linguistic intelligence and creative thinking. In addition, this research aims to analyze how linguistic intelligence influences creative thinking. This research was conducted at MAN 1 Serang City, Indonesia. The data analysis method was carried out using regression. The result of this research shows that there is an influence that linguistic intelligence has a significant influence on creative thinking. Linguistic intelligence involves mastery of language, including understanding grammar, vocabulary, and sentence structure can form the basis for someone to communicate clearly and effectively and can use various figures of speech, similes, or analogies to make their writing livelier and more interesting. Linguistic intelligence helps connect ideas that may not be directly related, see problems from different points of view, and design strong and interesting narratives. Thus, it can be concluded that linguistic intelligence has an influence on creative thinking and is an important component in the development of innovative ideas and creative problem-solving.